Strategi Mitigasi Wabah COVID-19 dalam Menjaga Keberlangsungan Operasional - Ilham, Ilham; Muin, Husain; Kotta, Husni; Wibowo, Dwiprayogo (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. The COVID-19 pandemic prompted mining companies to adopt adaptive strategies to maintain operational sustainability. PT X, a nickel mining company in Southeast Sulawesi, successfully sustained its production targets despite worker mobility restrictions and increased health risks. This study analyzes the managerial mitigation measures implemented and their impact on operational stability during the pandemic. A qualitative approach was employed through in-depth interviews, observations, documentation, and spiral model analysis. The findings indicate that the company applied multilayered mitigation policies covering pre-event to resolution phases, guided by disaster risk assessment, occupational safety, operational security, and sustainability principles. Key strategies included strengthened leadership and crisis communication, health-protocol-based human resource management, optimization of supporting services, CSR programs, financial safeguards, and updated disaster SOPs. These strategies effectively reduced COVID-19 transmission risks, ensured employee well-being, and maintained production consistency. This study highlights the importance of adaptive management–based disaster preparedness in the extractive industry. Abstrak. Penetapan pandemi COVID-19 sebagai bencana nasional mendorong perusahaan pertambangan menerapkan strategi adaptif untuk menjaga keberlanjutan operasional. PT X, perusahaan pertambangan nikel di Sulawesi Tenggara, mampu mempertahankan target produksi meskipun menghadapi keterbatasan mobilitas pekerja dan peningkatan risiko kesehatan. Penelitian ini bertujuan menganalisis tindakan mitigasi manajerial serta dampaknya terhadap stabilitas operasional selama pandemi. Penelitian menggunakan pendekatan kualitatif melalui wawancara mendalam, observasi, dokumentasi, dan analisis model spiral. Hasil penelitian menunjukkan bahwa perusahaan menerapkan kebijakan mitigasi berlapis yang mencakup fase pra-peristiwa hingga resolusi, dengan berlandaskan penilaian risiko, keselamatan kerja, keamanan operasional, dan keberlanjutan. Strategi utama meliputi penguatan kepemimpinan dan komunikasi krisis, manajemen SDM berbasis protokol kesehatan, optimalisasi layanan pendukung, program CSR, pengamanan keuangan, serta pembaruan SOP kebencanaan. Strategi tersebut efektif menekan risiko penularan COVID-19, menjaga kesejahteraan karyawan, dan mempertahankan konsistensi produksi. Studi ini menegaskan pentingnya manajemen adaptif dalam kesiapsiagaan bencana di industri ekstraktif.